Associations between skeletal muscle mass index, nutritional and functional status of patients with oesophago-gastric cancer. (December 2019) - Lidoriki, Irene; Schizas, Dimitrios; Mpaili, Eustratia; Vailas, Michail; Sotiropoulou, Maria; Papalampros, Alexandros; Misiakos, Evangelos; Karavokyros, Ioannis; Pikoulis, Emmanouil; Liakakos, Theodoros
Summary: Background and aims: Cancer patients frequently suffer from disease-related malnutrition and functional decline. The aim of the current study is to investigate the association between traditional methods of nutritional assessment (unintentional weight loss, Patient Generated-Subjective Global Assessment, anthropometric measurements), functional assessment and muscle mass assessment in oesophago-gastric cancer patients prior to surgery. Methods: A cross-sectional study was performed in 108 consecutive patients with oesophageal and gastric cancer who were admitted for surgery in the First Department of Surgery, Laikon General Hospital, Athens, Greece. The assessment of muscle mass was based on preoperative Skeletal Muscle Mass Index (SMI) values. The assessment of malnutrition was based on the Patient Generated Subjective Global Assessment, whereas laboratory markers and anthropometric measurements were also recorded. Muscle strength and physical performance were evaluated by measuring patients' handgrip strength and gait speed respectively. Results: 76.8% of the study sample were severely malnourished and moderately or suspected of being malnourished, while the prevalence of low muscle mass was 49.1%. Age was significantly higher in low SMI patients compared to normal SMI individuals (67.2 ± 9.2 vs 60 ± 10.8, p < 0.001). Albumin was significantly lower in low SMI compared to normal SMI patients, as well as BMI, mid-upper arm circumference, calf circumference and corrected mid arm muscle area. Moreover, malnourished patients exhibited higher rates of low muscle mass (57.8% vs 42.2%, p = 0.022) than well-nourished patients. SMI was also significantly correlated with patients' handgrip strength and gait speed. Conclusions: Low muscle mass is strongly correlated with malnutrition and should be taken into consideration when evaluating the nutritional status of patients with oesophago-gastric cancer.